Enhancing The Effectiveness Of Quality Control System Using Lean Six Sigma Approach - Mohd Hashim, Nurul Nasreen (2019)
In the manufacturing industry, intense competition and more complex customer needs and demands have forced entire industries and organisations to continuously improve the quality of their products, as well as the Small and Medium Enterprise (SME) industry. A good Quality Control (QC) system is the one of the factors that a company should be taking care of in delivering the best products quality and services in order to overcome the other competitors and gain customer’s loyalty. In this project, the company realises the need to enhance the effectiveness of their Quality Control (QC) system due to inconsistent judgment and repeated problems. Due to this problem, it could lower the production effectiveness and high reject and rework cases. The aim of this project is to enhance the effectiveness of the current Quality Control (QC) system by using Lean Six Sigma approach. In order to achieve the aim, there are two objectives that need to be achieved; (i) To identify the gaps between the current Quality Control (QC) system that used in the company and Quality Control (QC) system in theory and (ii) To enhance the effectiveness of current Quality Control (QC) system by eliminating and reducing the gaps. This project has been conducted using Lean Six Sigma approach which is the DMAIC methodology that consists of five stages DefineMeasure-Analyse-Improve-Control. Analysis of the results shows that (i) Only certain process in the production line of flexible link that have QC inspection, (ii) High potential inspection error based on experience which is absent of standard references for the visual inspection, (iii) Company does not follow the acceptance sampling theory. In conclusion, the effective of current QC system at the company can be enhanced through the implementation of acceptance sampling based on theory. Furthermore, the development of standard references for QC inspection at the production process is essential for the enhancement of QC system.